Will Women Save the World? The Ecological Civic Activity of Girls and Women from Generation Z Representing ICT and STEM - Chmura-Rutkowska, Iwona; Kozłowska, Agnieszka (Wydawnictwo Naukowe UMK, 2023)
The subject of the study is the gender gap in the environmental activism of young people from generation Z, related to the ICT and STEM sector, which plays a key role in the ecological transformation. Women are, according to world literature, more ecological than men in thinking, motivation and actions. The aim of the study was to check whether and to what extent this regularity applies to Poland and the masculinized ICT sector, where women constitute only about 20% of employees, and also what is the relationship between the level of environmental activism, environmental awareness and environmental behavior in the private sphere. The research sample consisted of 637 people born between 1995 and 2010 (Generation Z): 381 women (59.8%), 247 men (38.8%) and 9 non-binary people (1.4%). The data was taken from an extensive study carried out for the report on the values of ICT and STEM sector related young people from the generation Z. From the raw database, questions were extracted as indicators of awareness (15 questions on the NEP scale), ecological knowledge, sense of influence on counteracting the ecological crisis, risk perception of ecological threats, ecological behavior in the private sphere, and ecological activism (environmental behavior in the civic sphere). The data analysis included: (1) calculation of the NEP Index (2) frequency tables, including cross-tabs for all variables broken down by gender, (3) testing gender differences (Student’s t for continuous variables and Pearson’s Chi-square for ordinal and nominal variables) and (4) testing the relationship between selected variables and the level of environmental awareness (one-way ANOVA or t-test). Women turned out to be more environmentally aware than men (NEP Index 0.70 vs. 0.57), had more knowledge, a greater sense of influence on combating the ecological crisis, and greater faith in the effectiveness of the institutional activities in this area; showed greener behavior in their private lives and greater environmental activism. The ANOVA analysis showed that, with the exception of two variables, the surveyed areas of civic activity were proportionally related to environmental awareness: the higher the level of environmentalism, the higher the mean on the NEP scale. Almost all examined differences were statistically significant at p level < 0.001.
Keywords: ecological civic activity; green citizenship; gender gap; NEP scale; generation Z; ICT STEM